Marketing strategy of RSPL Health BD Ltd. for launching Uniwash - Shakil, Md. Didarul Haque (BRAC Univeristy, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.